Pharmacokinetic and pharmacodynamic similarity evaluation between an insulin glargine biosimilar product and Lantus® in healthy subjects: Pharmacokinetic parameters of both parent insulin glargine and M1 were used as endpoints - Wang, Yiya; Zhou, Ying; Ding, Juefang; Li, Xianjing; Guo, Fengxue; Zhang, Jianfei; Ding, Li (Frontiers in Pharmacology, 2022)
Insulin glargine is a long-acting insulin analog, which plays an important role in the treatment of diabetes mellitus. Biosimilar products of insulin glargine can provide patients with additional safe, high-quality and potentially cost-effective options for treating diabetes. This article presents a randomized, double-blind, single-dose, two-treatment, four-period, replicate crossover, euglycemic clamp study which was designed to evaluate the PK and PD similarity between the recombinant insulin glargine developed by Wanbang (test) and Lantus® (reference) in healthy volunteers. Subjects received subcutaneous administration of the insulin glargine formulation (0.4 U/kg) on two occasions for the test and reference drug respectively, and a 20% dextrose solution was infused at variable rate to clamp the blood glucose concentrations at 0.3 mmol/L below the subjects fasting glucose for 24 hours. Taking advantage of the improved sensitivity of the bioanalytical method applied and the solution of matrix stability problem, the parent insulin glargine was determined in the vast majority of plasma samples using a fully validated UHPLC-MS/MS method. The PK characteristics of the parent insulin glargine was revealed for the first time: after subcutaneous injection, concentrations of the parent insulin glargine increased to a relative high level within 3 hours, then a relatively flat concentration-time profile lasting to at least 12 h post-dose was observed. For the first time, the pharmacokinetic parameters of the parent insulin glargine were used as endpoints for similarity evaluation, which complied with the regulatory guidance better and made the similarity conclusion more powerful. The ratios of geometric means of all PK and PD endpoints were close to 100.00%. For the PK endpoints (AUC0-24h, Cmax, AUC0-12h, and AUC12-24h of the parent insulin glargine and its metabolite M1), the 90% confidence intervals of geometric mean ratios of test to reference were entirely contained within 80.00%–125.00%. For the PD endpoints (AUCGIR(0–24h) , GIRmax, AUCGIR(0–12h), and AUCGIR(12–24h)), the 95% confidence intervals of geometric mean ratios of test to reference were entirely contained within 80.00%–125.00%. Based on the above results, it can be concluded that the PK and PD characteristics of the biosimilar drug developed by Wanbang are similar to those of Lantus.